MEKANISME PELAKSANAAN JAMINAN SOSIAL BPJS KETENAGAKERJAAN BAGI PEKERJA DI PT. RIMBA MUJUR MAHKOTA - Ayu Sundari; Tri Reni Novita (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the implementation of BPJS employment in legal protection, constraints, and efforts in providing social security for workers at PT. Rimba Mujur Mahkota. This research was conducted at PT.Rimba Mujur Mahkota in Natal area, Mandailing Natal Regency, North Sumatra.Data collection techniques are in the form of interviews and documentation.The data that has been obtained from the results of the research will then be collected and analyzed descriptively, namely an analysis that describes the content and will be discussed in the form of an elaboration by giving meaning according to the applicable legislation so as to arrive at conclusions based on this research. From the results of the study it was found that: PT.Rimba Mujur Mahkota 1) There is no violation of the fulfillment of Article 14 of Law Number 24 of 2011, because all workers at PT.Rimba Mujur Mahkota participates in BPJS Employment.2) Has given social security rights to all workers at PT.Rimba Mujur Mahkota. Efforts made by BPJS Employment so that workers at PT.Rimba Mujur Mahkota provides social security benefits, namely, Carrying out program functions provided by BPJS Employment, namely Work Accident Protection, Old Age Protection, Pension Protection, and Death Protection. Legal protection for workers of PT.Rimba Mujur Mahkota who is experiencing social welfare problems, such as health, and old age is to provide social security organized by BPJS Employment.As stipulated in the Law of the Republic of Indonesia Number 24 of 2011 concerning the Social Security Administering Body (BPJS).